Proporsi Susu Kedelai dan Buah Kurma (Phoenix Dactylifera L) terhadap Mutu Sensori Panna Cotta - Julia Rahmatiyasyafitri Habibah; Ita Fatkhur Romadhoni; Lucia Tri Pangesthi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to evaluate the optimal proportion between soy milk and dates in the preparation of panna cotta as an innovative food product that considers nutritional value. The innovation is intended to create a dessert alternative that is not only delicious but also nutritionally rich and suitable for consumers seeking healthy or plant-based food options. The specific objectives of this study are: (1) To determine the best sensory quality based on variations in soy milk proportions in the panna cotta, (2) To identify the best sensory quality based on different proportions of dates, (3) To examine the interaction between soy milk and dates on the sensory qualities of the panna cotta, and (4) To analyze the nutritional content of the best panna cotta formulation in terms of calories, carbohydrates, protein, and fat. This research employed an experimental method with a factorial design to observe the individual and interactive effects of the ingredients on sensory attributes (color, aroma, texture, and taste) and nutritional content. The results showed that: (1) The best formulation was obtained from the combination of 75% soy milk and 75% dates based on panelist evaluations. (2) Soy milk had a significant influence on the sensory attributes of color, aroma, texture, and taste. (3) Dates had a significant effect on the texture. (4) There was a significant interaction between soy milk and dates on the sensory qualities of color and texture, indicating a synergy that enhances the overall product appeal. (5) The nutritional analysis of the best panna cotta revealed the following composition per 100 grams: 216.50 kcal of energy, 8.82% protein, 7.05% fat, and 27.08% carbohydrates. These findings suggest that panna cotta made with a combination of soy milk and dates can serve as a healthy, nutritious, and innovative dessert option, appealing both in flavor and in nutritional profile, particularly for health-conscious or plant-based consumers.